The economic benefits of worksite wellness programs - Lynch, Krista (Kansas State University, 2014)
Comprehensive worksite wellness programs were first introduced in the United States in the late 1970s and early 1980s, with the goals of improving health, reducing health care expenditures, and demonstrating senior management’s commitment to the health and well-being of workers (Ozminkowski et al, 2002). As the annual cost of employer-sponsored family health coverage increased four percent between 2012 and 2013 (Kaiser Family Foundation, 2013), many companies are turning to worksite wellness programs. Wellness programs have shown not only to reduce health care costs, but also decrease absenteeism and increase employee satisfaction. The studies on the benefits of wellness programs are not conclusive; there seems to be a general lack of good data collection and analysis. This report discusses what determines an employer’s likelihood of offering a wellness program, what determines an employee’s participation in a wellness program, and a benefits analysis of wellness programs.
Keywords: Wellness program; Worksite; Employer sponsored; Economic benefits; Obesity cost; Absenteeism; Economics (0501); Health Care Management (0769)